GLACIAL LAKE TSUNAMI OF 13 OCTOBER 2000 ON "EL ALTAR" VOLCANO OF ECUADOR - Theofilos Toulkeridis; Izar Sínde-González; Jheny Orbe (Science of Tsunami Hazards, 2022)
There are a number of unusual tsunamis, which occur within the continents rather than in the oceans, named inland tsunamis. One of these rare occasions occurred in the morning of the Friday the 13th October 2000 in a volcanic glacial lake of the horseshoe shaped extinct El Altar volcano in central Ecuador. A detailed mapping of available air photos and satellite images have been reviewed and evaluated in order to reconstruct the catastrophic event of 2000 and a previous one, evidencing that climate change and the associated subsequent reduction of the glacial caps have been responsible for the disassociation of a huge mass of rock(s), of which separation has resulted to an impact in the volcanic lake by an almost free fall of some 770 meters above lake level ground. This impact generated a tsunami wave capable to reach an altitude of 125 meters about the lake ́s water level and leave to lower grounds killing some ten people and hundreds of animals with a mixture of a secondary lahar and debris avalanche. We tried to explain how the fall has occurred with some theoretical considerations, which resulted to imply that the rock hit at least once, probably twice the caldera wall prior lake impact. Such phenomena, even if rare, need to be better monitored in order to avoid settlements in potential areas in the reach of such devastating waves and subsequent avalanches, even more so, when due to climate change the accumulation of water in such lakes increases and the corresponding subglacial erosion and corresponding disassociation of lose rock material may set free more rocks with substantial volumes.